2002
DOI: 10.1007/s102380200004
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Inflammatory and lipid factors share an important role in atherosclerosis. Recent studies showed the concomitant presence and increase of complement components and lipids both in the atherosclerotic plaque and the circulating blood. The aim of this study was to examine the relationship between the complement system and lipid disorders. We evaluated the circulating complement terminal complex C5b-9, a clear sign of complement activation, in three groups of 30 patients the first with hypercholesterolemia, the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
2
6
0
Order By: Relevance
“…Changes in sC5b-9 levels after treatment were inversely related to changes in HDL-C and total cholesterol levels. This is in line with previous studies demonstrating an inverse relationship between sC5b-9 and HDL-C [40]. This might be explained by the relationship between complement activation and inflammation, as both HDL-C and total cholesterol are known to increase with decreasing disease activity in IRDs [41].…”
Section: Discussionsupporting
confidence: 92%
“…Changes in sC5b-9 levels after treatment were inversely related to changes in HDL-C and total cholesterol levels. This is in line with previous studies demonstrating an inverse relationship between sC5b-9 and HDL-C [40]. This might be explained by the relationship between complement activation and inflammation, as both HDL-C and total cholesterol are known to increase with decreasing disease activity in IRDs [41].…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, the analysis of cultured endothelial cells has shown the blockage of membrane attack complex assembly by HDL [56,57]. On the contrary, in vivo studies have revealed a negative correlation between the HDL level and the concentration of the circulating terminal complex C5b-C9 in plasma [58]. These data are in contrast to the results of proteomic analysis.…”
Section: Immune Reactionsmentioning
confidence: 83%
“…The complement system has been observed to directly participate in inflammation in atheromas [ 194 ], regulated by vitronectin and clusterin [ 195 ]. Likewise, in vitro assays have shown HDL can prevent organization of the membrane attack complex [ 196 , 197 ] and share a negative correlation with C5b-9 levels [ 198 ], promoting complement inhibition.…”
Section: Proteomics and Lipidomics: A Focus On Hdlmentioning
confidence: 99%